(untitled) (National Administration Journal, 2025)
This work reviews the main aspects of benchmarking in general surgery, based on a literature revision considering the basic concepts of this practice, its development, the impact on patient care quality and the methodologies used to measure and compare the performance of the surgical services. According to the finds there is an evident gap in the implementation of this methodology in public surgical services in Costa Rica, and an opportunity for improvement through the application of these practices to determine basic standards of care, as well as to generate processes which allow for the parametrization of healthcare.